Advantages of Recognizing Uncertainty During the Planning Phase of Engineering Projects in Developing Countries: A Case Study of Oil and Gas Private Companies in Libya - Abdel Latif A. Mohamed El Gamoudi; Tarek M. M. Khalifa (African Journal of Advanced Pure and Applied Sciences, 2024)
Identifying uncertainties during the planning phase is essential for the success of engineering projects, particularly within the context of private oil and gas companies in Libya, where fluctuating market conditions and regulatory environments add complexity to project planning. This research investigates the types of uncertainties that commonly arise during the planning phase of engineering projects, aiming to identify strategies to mitigate potential failures and improve project outcomes. A survey was conducted of 25 professionals actively involved in various stages of engineering projects, using a structured questionnaire to gather insights into the nature and impact of these uncertainties. The collected data was analyzed using Excel software, focusing on quantitative trends and respondents’ qualitative feedback. The results reveal that planning fallacies—such as overly optimistic timelines, underestimation of costs, and incomplete risk assessments—are among the most prevalent issues. By basing project plans on realistic assessments, leveraging historical data, and incorporating relevant information from past projects, project managers can enhance their ability to anticipate challenges and adapt their strategies accordingly. The study highlights that effective identification and management of uncertainties during the planning phase is crucial for project managers to navigate dynamic conditions, optimize resource allocation, and ensure successful project execution. These findings offer practical recommendations for improving planning practices in the Libyan oil and gas sector and contribute to a broader understanding of managing uncertainty in complex engineering environments.